Finite Frequency H∞Control of Two-Dimensional Continuous Takagi-Sugeno Systems - Zoulagh, T (Institute of Electrical and Electronics Engineers Inc., 2022)
This paper solves a state feedback H∞ control issue for two-dimensional (2D) nonlinear continuous systems described by Takagi-Sugeno (T-S) fuzzy model by using a finite frequency (FF) approach. In particular, a Roesser model is investigated by employing the Generalized Kalman Yakubovich Popov (GKYP) lemma. New conditions guaranteeing the FF H∞ control and the bounded-input-bounded-output (BIBO) stability of the closed-loop system are established in terms of Linear Matrix Inequalities (LMIs). These stipulations extend minimal conservative results not only by getting the controller gain, but also in terms of H∞ norm and closed-loop states convergence when compared with the entire frequency (EF) design and the uncontrolled states. To exhibit the superiority of the submitted strategy, an implementation to a simulated system is thus presented. © 2022 IEEE.